Copper-Content Dependent Structural and Electrical Properties of CZTS Films Formed by “Green” Colloidal Nanocrystals - Volodymyr Dzhagan; Oleksandr Selyshchev; Serhiy Kondratenko; Nazar Mazur; Yevhenii Havryliuk; Oleksandra Raievska; Oleksandr Stroyuk; Dietrich R. T. Zahn (Electronic Materials, 2022)
Thin films of colloidal CZTS nanocrystals (NCs) synthesized using a “green” approach in water with a variation of the copper-to-tin ratio are investigated by Raman scattering, mid-infrared (molecular vibrations) and near-infrared (free carrier) absorption, X-ray photoemission spectroscopy (XPS), electrical conductivity, and conductive atomic force microscopy (cAFM). We determined the effect of the actual Cu content on the phonon spectra, electrical conductivity, and spectral parameters of the plasmon band. An increase in the electrical conductivity of the NC films upon annealing at 220 °C is explained by three factors: formation of a CuxS nanophase at the CZTS NC surface, partial removal of ligands, and improved structural perfection. The presence of the CuxS phase is concluded to be the determinant factor for the CZTS NC film conductivity. CuxS can be reliably detected based on the analysis of the modified Auger parameter of copper, derived from XPS data and corroborated by Raman spectroscopy data. Partial removal of the ligand is concluded from the agreement of the core-level XPS and vibrational IR spectra. The degree of lattice perfection can be conveniently assessed from the Raman data as well. Further important information derived from a combination of photoelectron and optical data is the work function, ionization potential, and electron affinity of the NC films.